Brand awareness dan Celebrity Endorser sebagai Penentu Keputusan Konsumen: Studi pada Produk Wardah di Toko Jakarta Geudong, Aceh Utara - Rauzi Ramazalena (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the influence of brand awareness and celebrity endorser on the purchasing decisions of Wardah products at Toko Jakarta Geudong, North Aceh. The research employed a quantitative approach, involving 96 respondents and using SPSS 25.0 for data analysis. The results indicate that brand awareness has a partial effect on purchasing decisions (t-value = 2.825 > t-table = 1.661; sig = 0.002), as does the celebrity endorser variable (t-value = 3.417 > t-table; sig = 0.000). Simultaneously, both variables have a significant effect on purchasing decisions (F-value = 31.321 > F-table = 3.09; sig = 0.000). The coefficient of determination (R²) is 0.410, indicating that 41% of the variation in purchasing decisions is explained by the two independent variables, while the remaining 59% is influenced by other factors outside this study.